Hur kan man få fler att använda infartsparkerinar? - Olsson, Anna-Lena Lindström (Proceedings from the Annual Transport Conference at Aalborg University, 2003)
Problems associated with traffic, such as traffic congestion and pollution, have occurred in major urban areas in particular due to the increased use of cars. One possible way to reduce the use of cars is to replace commuter trips by car with other modes of transport, such as a combination of car and public transport called Park & Ride. The aim of this thesis was to understand more about factors influencing the choice of mode and to find measures that could attract car drivers to Park & Ride. A stated preference survey has been conducted in order to quantify some standard factors. The factors used in this stated choice experiment were: security at the lot, availability of spaces at the parking lot, costs at the parking lot and walking distances between the parking space and the station. The results indicate that security at the Park & Ride facility is important. Both sexes assign a high value to secure parking, but women are more willing to pay for lights at an unguarded parking lot. The results reveal that park-ing facilities, such as free parking and short distance between parking place and work at work, influence people’s choice of mode. A general conclusion is that there is potential for increasing the use of Park & Ride facilities, especially among women and respon-dents over 30 years.